Resolving Network Issues Using Augmented Reality and Virtual Reality - Anireddy, Srilakshmi; Mantri, Archana (Journal of Engineering Education Transformations, 2021)
Networking is a critical and essential commodity in today’s digital world, as it establishes communication between people at remote locations. Routers, switches, cables, etc. are the essential devices of any network. Network technicians use these devices to set up the network at homes, offices and public places. In a situation of any network issue, the end-user is dependent upon the network service provider to resolve the issue as the end-user has not sufficient knowledge about the network devices. However, with the help of Augmented Reality (AR) and Virtual Reality (VR) technology, end-user can be provided with the basic training or knowledge to operate the network devices. In this paper, an AR or VR based learning environment is proposed, for providing the knowledge about different network devices and their connections. While this elementary knowledge will add to the awareness of the enduser about networking, it would also enable reducing the cost and time of the end-user and network technicians.